2021
DOI: 10.1002/solr.202100255
|View full text |Cite
|
Sign up to set email alerts
|

Achieving a Record Open‐Circuit Voltage for Organic/Si Hybrid Solar Cells by Improving Junction Quality

Abstract: Nanostructured Si has attracted widespread attention due to its strong light‐harvesting ability, which is beneficial to improve the performance of solar cells. However, the poor contact of the organic/nanostructured Si interface and the large number of recombination centers on the Si surface result in an unsatisfactory open circuit voltage (VOC) and fill factor (FF) of the device. Herein, a simple and versatile method, Si nanowires modified with tetramethylammonium hydroxide (TMAH) and poly(3,4‐ethylenedioxyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…As shown in Figure 4 e, the improvement in quantum efficiency (EQE) is explained by the fact that the interface contact quality is enhanced. The Raman spectrum in Figure 4 f shows that the energy band at 1400–1450 cm −1 is attributed to the C α = C β stretching vibration of the five-membered ring of PEDOT:PSS shifting to a lower energy and becoming wider [ 4 ]. This indicates that the conformation of the PEDOT:PSS chain changes from a curled to a more linear or extended curled structure after the introduction of the DEP coating, which is beneficial to the conductivity of the PEDOT:PSS thin films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4 e, the improvement in quantum efficiency (EQE) is explained by the fact that the interface contact quality is enhanced. The Raman spectrum in Figure 4 f shows that the energy band at 1400–1450 cm −1 is attributed to the C α = C β stretching vibration of the five-membered ring of PEDOT:PSS shifting to a lower energy and becoming wider [ 4 ]. This indicates that the conformation of the PEDOT:PSS chain changes from a curled to a more linear or extended curled structure after the introduction of the DEP coating, which is beneficial to the conductivity of the PEDOT:PSS thin films.…”
Section: Resultsmentioning
confidence: 99%
“…Si/poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS) heterojunction solar cells (HSCs) are promising candidates for commercial photovoltaic cells, as they can be fabricated using simple low-cost preparation techniques and achieve high output efficiency [ 1 , 2 , 3 , 4 , 5 ]. Previous studies have shown that the typical average reflectivity of traditional pyramid-textured Si substrates exceeds 12% in the 400–1000 nm wavelength range [ 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…surface treatment on nanostructured Si and doping of PEDOT: PSS [159] in order to increase the interface wettability. However, there are fewer similar reports on III-V NWSCs.…”
Section: Nw Array Solar Cellsmentioning
confidence: 99%
“…To address these problems, optimization approaches at different levels have been proposed, including: 1) material optimization, which involves enhancing the electrical conductivity of polymers, [161][162][163] improving the quality, and doping engineering of semiconductor layers [22,78,164] ; 2) structure optimization, which involves geometric optimization, band structure regulation (e.g., introduction of BSF/FSF, [29] introduction, or modification of HTL/EBL [110,111] ), and introduction of optical functional layers (e.g., window layer/ARC [31,33] ); and 3) interface engineering including surface passivation for semiconductor layers [38,165,166] and conformal contact improvement for polymer layers. [159] Herein, we focus on electrical conductivity enhancement for polymers and surface passivation for semiconductor layers. Discussions on the other optimization approaches can be found in the literature or the preceding part of this review.…”
Section: Optimization Pathways For Efficiency Enhancementmentioning
confidence: 99%
“…Electrode work functions are decisive for interfacial energy-level alignment and for the performance of hybrid (opto-)electronic devices. [1][2][3][4] The conductive polymer poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is frequently used as a hole-injecting electrode in devices such as light-emitting diodes, [5][6][7] photovoltaic devices, [2,[8][9][10] and field-effect transistors. [11,12] The basis of these widespread applications of PEDOT:PSS thin films is their high and tunable work function which ranges-depending on the PEDOT:PSS formulation, substrates, processing conditions, etc.-from 4.7 to 6.1 eV.…”
Section: Introductionmentioning
confidence: 99%